Answer:
9
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Step-by-step explanation:
<u>Step 1: Define</u>
3(y + 2)² + 3x
x = 2
y = -1
<u>Step 2: Evaluate</u>
- Substitute: 3(-1 + 2)² + 3(2)
- Add: 3(1)² + 3(2)
- Exponents: 3(1) + 3(2)
- Multiply: 3 + 6
- Add: 9
Answer:
0.875
Step-by-step explanation:
divide 7 by 8 to get the answer
Answer:
1.
centre(h,k)=(-13,9)
radius (r)=6
we have
equation of the circle is
(x-h)²+(y-k)²=r²
(x+13)²+(y-9)²=6²
x²+26x+169+y²-18y+81=36
x²+y²+26x-18y+169+81-36=0
x²+y²+26x-18y +214=0
is a required equation of the circle.
2.
centre(h,k)=(1,-1)
radius (r)=11
we have
equation of the circle is
(x-h)²+(y-k)²=r²
(x-1)²+(y+1)²=11²
x²-2x+1+y²+2y+1=121
x²+y²-2x+2y=121-2
x²+y²-2x+2y=119
is a required equation of the circle.
U will first need to collect the like terms,
x+16>-5x+4
-5x will go to the other side becoming 5x while 16 while also cross the other side becoming -16
x+5x>4 -16
6x> when 4 is taken out from -16 it becomes - 12
6x>-12 when divided the answer obtained will be -2
In order it goes like this
- 4^ x - 1 = 3^ (-x) - 2
- 3 x + 6 = 2^ x + 1
3^ x - 3 = 2 x - 2
so the question is the answer